Whatsapp e seleção de pautas: o processo de gatekeeper no programa O Povo no rádio e as estratégias do ouvinte repórter para emplacar pautas na programação - Monte, Rachel Gomes Braga (2019)
Despite walking hand in hand with technological, cultural, and social transformations since its inception, the essence of radio remains with the same (or more potent) force: the listener. Brecht (2005), early on, already predicted: listeners must be the major suppliers of radio. And so, from letters to WhatsApp, we reach a level where the listeners not only participate in the programming: they criticize, suggest, praise, interact, modify and are present in many of the processes. And journalists are still there, side by side, retaining the function of selecting the news, ascertaining the true information, with the challenge of fulfilling their role of reporting correctly in an era where many have the tools to do so. This research seeks to analyze the strategies used by what we define as Listener Reporter in the program O Povo no Radio, from Radio O POVO CBN, to record guidelines in the station. For this, we use the concepts of types of Radio Interaction (XAVIER, 1998) (LOPEZ; QUADROS, 2015), Criteria of Noticeability (WOLF, 2009), Acts and Marks of Journalism (STEARNS, 2013; FÍGARO, 2018) to understand how the station's gatekeepers (WOLF, 2009) forward the guidelines suggested by listeners. To do this, we use the methodological procedures Participant Observation and Content Analysis to analyze messages sent to the broadcaster's WhatsApp, during 22 business days, between May 2 and May 31, between 6 am and 10:20 am. The application of the theoretical basis to the data obtained through qualitative and quantitative research proved that the application of the criteria of news by journalists is a subjective and automatic process, being subject to structural and organizational conditions of the journalistic company. We also noticed the predominance of the importance criterion, through the variables Number of People Involved and Impact on the Nation in the gatekeeping of journalists, and that the listeners use, mainly, as a strategy to place guidelines, journalistic elements linked to the basic principles of the profession, such as the objective description of the problem and the exact identification of the event. Added to this are tools made available by WhatsApp, such as pictures, which is another feature used by listeners when it comes to assigning an agenda to the broadcaster. Keywords: Radio journalism. WhatsApp. Agenda suggestion. Strategies. Listener.